Beta cell regeneration and antidiabetic potential of Ficus sycomorus and Zanthoxylum chalybeum - Kimani, Clare Njoki (Stellenbosch : Stellenbosch University, 2023)
Kimani, Clare Njoki. 2023. Beta cell regeneration and antidiabetic potential of Ficus sycomorus and Zanthoxylum chalybeum. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/550675c3-045c-41ab-84f1-29d1abb076b6